2021
DOI: 10.1029/2021gl095341
|View full text |Cite
|
Sign up to set email alerts
|

Copernican‐Aged (<200 Ma) Impact Ejecta at the Chang'e‐5 Landing Site: Statistical Evidence From Crater Morphology, Morphometry, and Degradation Models

Abstract: Chang'e-5 (CE-5) is China's first lunar sample-return mission. It landed in northern Oceanus Procellarum on December 1, 2020, at 43. 06°N, 51.92°W (Wang et al., 2021). 1,731 g of lunar regolith was collected and are currently under laboratory investigations.The CE-5 site (Statio Tianchuan, IAU-name) is located within Eratosthenian-aged intermediate-Ti mare basalts (labeled as Em4/P58 by Qian, Xiao, Wang, et al., 2021), with an average thickness of ∼51 m, a total volume between 1,450 and 2,350 km 3 (Qian, Xiao,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…The exotic ejecta in CE‐5 regolith are mainly from five proximal and four distant craters (Qian, Xiao, Head, et al., 2021; Qian, Xiao, Wang, et al., 2021). The five proximal craters (<1 km) are too small to fit with our calculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exotic ejecta in CE‐5 regolith are mainly from five proximal and four distant craters (Qian, Xiao, Head, et al., 2021; Qian, Xiao, Wang, et al., 2021). The five proximal craters (<1 km) are too small to fit with our calculations.…”
Section: Discussionmentioning
confidence: 99%
“…And also, the average thickness of lunar regolith layer for maria and highlands areas are only ∼5 and 12 m, respectively (Shkuratov & Bondarenko, 2001), whereas the excavation depth of large impact craters can be hundreds of meters to several kilometers (compiled data from Qian, Xiao, Head, et al. (2021) and Qian, Xiao, Wang, et al. (2021)), thus the low‐porosity bedrock can be excavated, which could be the host for seifertite and stishovite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short space exposure history of CE-5 lunar soil indicated that it endured relatively modest space weathering alterations. 19 This provides the necessary conditions for preserving information regarding the initial evolutionary stage of lunar soil.…”
Section: Introductionmentioning
confidence: 99%
“…The CE-5 lunar samples can be regarded as the weathering and mixing products of local rocks (∼91 wt%, , with minimal ejecta materials from Harpalus, Copernicus, and Aristarchus craters (Qian, Xiao, Head, Wöhler, et al, 2021). Previous research (Che et al, 2021;He et al, 2022;Jiang et al, 2021;C.…”
mentioning
confidence: 99%